1988
DOI: 10.1039/dt9880002033
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)-assisted hydrolysis of 2,4,6-tris(2-pyridyl)-1,3,5-triazine. Part 1. Crystal structures of [bis(2-pyridylcarbonyl)amido](2-pyridylformamide)-copper(II) perchlorate monohydrate and [bis(2-pyridylcarbonyl)amido]-copper(II) perchlorate

Abstract: Copper( 11)-assisted Hydrolysis of 2,4,6-Tris(2-pyridyl)-I ,3,5-triazine. Part 1. Crystal Structures of [ bis(2-pyridylcarbonyl)amido] (2-pyridy1formamide)copper( 11) Perchlorate Monohydrate and [ Bis(2-pyridylcarbonyl)amido]copper( 11) Perchlorate t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 6 publications
3
34
0
Order By: Relevance
“…Mono-, di-(homo-and heteronuclear), and trinuclear complexes have been reported for various divalent and trivalent metal ions (M II = Cu II , Fe II , Mn II , Co II , Ni II , and Zn II ; M III = Fe III , Rh III ). [27][28][29][30][31][32][33] Among these, a ternary complex of copper(II) with one bpca -and another derivative formed during the hydrolysis process, namely 2-picolinamide, has been described. [28] The ptO 2 -anion is obtained by means of a Cannizzaro-type reaction of pyridine-2-carboxaldehyde and NaNCO in the presence of copper metal ion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mono-, di-(homo-and heteronuclear), and trinuclear complexes have been reported for various divalent and trivalent metal ions (M II = Cu II , Fe II , Mn II , Co II , Ni II , and Zn II ; M III = Fe III , Rh III ). [27][28][29][30][31][32][33] Among these, a ternary complex of copper(II) with one bpca -and another derivative formed during the hydrolysis process, namely 2-picolinamide, has been described. [28] The ptO 2 -anion is obtained by means of a Cannizzaro-type reaction of pyridine-2-carboxaldehyde and NaNCO in the presence of copper metal ion.…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30][31][32][33] Among these, a ternary complex of copper(II) with one bpca -and another derivative formed during the hydrolysis process, namely 2-picolinamide, has been described. [28] The ptO 2 -anion is obtained by means of a Cannizzaro-type reaction of pyridine-2-carboxaldehyde and NaNCO in the presence of copper metal ion. [34] Kawijara et al have described the ptN 2 -ligand, [35] which forms when ptz is mixed with copper(II) acetate at reflux in dry MeOH in the presence of NaClO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have described that coordination of one metal ion, especially Cu II , to tptz induces the hydrolysis of tptz to form bis(2-pyridylcarbonyl)amine and its complexes. [22,23] In order to use tptz as a ferromagnetic coupler between three transition metal ions we investigated whether complexes with tptz as a bridging ligand between three metal ions in bipyridine-like sites would be accessible (V in Scheme 1). Herein we report the reaction of tptz with an excess of Cu II ions.…”
Section: Introductionmentioning
confidence: 99%
“…However, in the presence of copper(II) ions, hydrolysis occurs under mild conditions to afford the highly stable bis(2-arylcarbonyl) amidocopper(II) species [Cu(bpcam)] + (tpymt) and [Cu(bpca)] + (tpyt) [4,5]. While other first-row transition metal ions are unable to cause this hydrolysis, it has recently been shown that Rh(III) promotes the hydrolysis of tptz yielding the same fragments [6].…”
mentioning
confidence: 99%